Traditional Chinese Medicine Intervenes Ventricular Remodeling Following Acute Myocardial Infarction: Evidence From 40 Random Controlled Trials With 3,659 Subjects - Zhang, Xiao-Xiao; Liang, Bo; Shao, Chang-Le; Gu, Ning (Frontiers in Pharmacology, 2021)
Objectives: We intend to conduct a meta-analysis on the systematic evaluation of traditional Chinese medicine (TCM) in the treatment of ventricular remodeling following acute myocardial infarction (AMI). Our findings may provide certain references for the clinical treatment of ventricular remodeling. Methods: A systematic literature search was conducted in PubMed, Web of Science, Cochrane Library, Embase, CNKI, Wanfang Data, CQVIP, and CBM before 20th July 2020. Data were analyzed using a random/fixed-effect model. Primary outcomes included the effectiveness and TCM syndrome score (TCMSS). Secondary outcomes included: (1) Echocardiography data, including the left ventricular end-diastolic diameter (LVEDD), left ventricular end-systolic diameter (LVESD), left ventricular end-diastolic volume index (LVEDVi), left ventricular end-systolic volume index (LVESVi), left ventricular end-diastolic volume (LVEDV), left ventricular end-systolic volume (LVESV), interventricular septum thickness (IVST), left ventricular posterior wall thickness (LVPWT), left ventricular ejection fraction (LVEF), E/A, stroke volume (SV) and wall motion score (WMS); (2) Serum indicators, including the B-type natriuretic peptide (BNP) or N-terminal pro B-type natriuretic peptide (NT-proBNP), and C-reactive protein (CRP) or high sensitivity CRP (hs-CRP); (3) Major adverse cardiovascular events (MACE) and other adverse events. Results: Forty RCTs involving 3,659 subjects were recruited. Our findings proved that a combination of TCM or TCM preparations with conventional Western medicine for preventing and reversing ventricular remodeling at post-AMI could remarkably enhance the total effectiveness and reduced TCMSS. Moreover, myocardial functions (LVEF, E/A, and SV), ventricular remodeling (LVEDVi, LVESVi, LVEDV, LVESV, LVEDD, LVESD, LVPWT, and WMS), serum levels of BNP and CRP, and MACE were significantly improved by the combination of TCM or TCM preparations with conventional Western medicine. Nevertheless, IVST and the incidence of other adverse events were comparable between control and experimental groups. Conclusion: The combination of TCM or TCM preparations and conventional Western medicine can alleviate the process of ventricular remodeling, enhance cardiac function and reduce the incidence of MACE in AMI patients.